Screening of Fungal Strains for Single-Culture Solid-State Fermentation of Liupao Tea - WU Xinhui, DU Jinjie, LIU Xiaochun, LIAO Kaibin, QIN Yuna, LIANG Weijie, ZHANG Lingzhi, LONG Zhirong, QIU Ruijin (Shipin Kexue, 2024)
In this study, 20 fungal strains isolated from Liupao tea were used for solid-state fermentation of sterilized raw Liupao tea from Cangwu Quntizhong. The fermentation performance of these strains was explored by sensory evaluation and biochemical analysis combined with principal component analysis (PCA) and strains that are able to significantly improve the quality of Liupao tea or impart new flavor to the tea were selected. The results showed that nine fungi with excellent fermentation performance were obtained, namely, Aspergillus tubingensis, A. niger, Penicillius manginii, A. keratitidis, A. ruber, A. intermedius, P. commune, A. amstelodami and Trichomonascus ciferrii. Moreover, A. tubingensis, A. niger, P. commune and A. amstelodami could significantly change the contents of 18 chemical components in tea samples. P. commune and A. amstelodami were identified as excellent starter cultures for Liupao tea fermentation. This study could provide a theoretical basis for the improvement of the fermentation process of Liupao tea and the development, innovation and quality improvement of tea products.